Acceptance and commitment coaching for music performance anxiety in adolescent singers - Paul, Anupa Elizabeth; Juncos, David G.; Winter, Debbie (Frontiers in Psychology, 2024)
Most of the anxiety disorders, particularly social anxiety, seem to develop either during childhood or adolescence. Adolescent singers who experience physical, mental and emotional changes along with voice change are particularly prone to the development of MPA. However, adolescence also seems to be an opportune time to instil healthy behaviours in singing students as they are more likely to remember these coping strategies, owing to the release of dopamine and the 'reminiscence bump' .The study aimed to determine if Acceptance and Commitment coaching could be used with adolescent singers with MPA and to record and analyse rich qualitative data in the form of participant interviews. As this period of a singer's life is wrought with inevitable anxiety development, the additional aim of the study was to develop a coaching framework which can be used by singing teachers in their practice. Mindset training for adolescents seems crucial to help them continue singing through puberty so they do not drop out of singing lessons or choir during voice change and identity development. If provided early during adolescence, When their perception of MPA symptoms and physiological and psychological arousal before a performance changed, their behaviour and reactions changed accordingly. The change took place over a period of time, which was characterised by discoveries about themselves, confusion in understanding new concepts and letting go of old habits. Interestingly, by the end of the coaching sessions, their preoccupation with pleasing the audience and appearing perfect on stage was replaced by a new-found delight in pursuing values and goals related to their singing. Along with this came the acceptance of themselves and others as individuals with the potential for growth and change and the capacity to learn from mistakes.This study marks the first investigation into the effectiveness of using of ACC as an intervention for MPA in adolescent singers undergoing puberty by a singing teacher. The results are promising and suggest that ACC is an effective MPA intervention for adolescent singers to cope with inevitable development-related anxieties and keep them engaged in the activity of singing during their pubertal years.